Hsa_circ_0051908 Promotes Hepatocellular Carcinoma Progression by Regulating the Epithelial–Mesenchymal Transition Process - Yinbing Wu; Huafei Tang; Shuzhong Cui; Quanxing Liao; Lisi Zeng; Yinuo Tu (Analytical Cellular Pathology)
Background/Aims. Circular RNAs (circRNAs) are often used for tumor diagnosis and treatment owing to their high stability, high expression abundance, and strong tissue specificity. The role of hsa_circ_0051908, a newly reported circRNA, in the development of hepatocellular carcinoma (HCC) is unknown. Materials and Methods. Hsa_circ_0051908 expression was determined using RT-qPCR. HCC cell proliferation, apoptosis, invasion, and migration were assessed using CCK-8 assay, EdU staining, TUNEL staining, flow cytometry, and transwell assay. The molecular mechanism was analyzed using western blotting. In addition, the role of hsa_circ_0051908 in tumor growth was evaluated in vivo. Results. Hsa_circ_0051908 expression was increased in both HCC tissues and cell lines. The proliferation, migration, and invasion of HCC cells were significantly decreased after hsa_circ_0051908 knockdown, while cell apoptosis was notably increased. Furthermore, we found that hsa_circ_0051908 silencing downregulated vimentin and Snail and upregulated E-cadherin. In vivo, hsa_circ_0051908 silencing significantly inhibited the growth of the tumor. Conclusions. Our data provide evidence that hsa_circ_0051908 promotes HCC progression partially by mediating the epithelial–mesenchymal transition process, and it may be used for HCC treatment.